Word-of-Mouth Marketing in the Music Industry: Are Record Labels Communicating Effectively With Their Target Market? - Hoak, Katherine (2006)
This study explores the importance of word-of-mouth (WOM) communications in the context of consumers discovery of new music. It begins with an overall review of WOM theory, including traditional word-of-mouth, viral marketing, online social networks, and consumer motivation to participate in WOM activities. Qualitative interviews, conducted with music industry professionals as well as consumers of music, are analysed in order to determine whether or not music companies are communicating effectively with consumers through WOM marketing. A disconnect is found between the way that record labels intend to interact with consumers and the way in which consumers perceive these actions. A proposal for more effective ways in which record labels can use WOM marketing is then laid out. Insights into the ways in which consumers discover new music and interact with one another on social networking sites are also addressed.